Revolutionizing agriculture: a review of smart farming technologies for a sustainable future - Mimansha Raj; M. Prahadeeswaran (Discover Applied Sciences)
Abstract This review critically examines the transformative potential of smart farming technologies in addressing the global food security challenge posed by climate change, rising populations, and dwindling resources. The study bridges existing research gaps by integrating findings across diverse technological domains—Artificial Intelligence (AI), Internet of Things (IoT), Unmanned Aerial Vehicles (UAVs), robotics, and deep learning—to present a unified perspective on Agriculture 4.0. Unlike previous studies that isolate individual innovations, this paper emphasizes their convergence in creating efficient, data-driven ecosystems. Findings reveal that AI-enabled models improved yield prediction by 20%, UAVs reduced water and fertilizer use by up to 96% and 40% respectively, and IoT-based smart irrigation systems enhanced crop productivity by 25%. The review also highlights successful applications such as disease diagnosis with over 90% accuracy, autonomous robots for precision farming, and aquaponic systems reducing water usage by 90%. Despite these advances, adoption is hindered by infrastructural, financial, and data governance challenges. By applying PRISMA methodology to analyze 63 high-impact studies from 2019 to 2024, this review proposes actionable pathways including policy incentives, scalable architectures, and capacity-building to democratize access and foster sustainability. This work contributes a comprehensive synthesis and practical roadmap for accelerating smart agriculture adoption in both developed and resource-constrained settings.